STRATEGI IMPLEMENTASI KURIKULUM: SUATU KAJIAN PERSPEKTIF TEORI DI SEKOLAH DASAR - H. SUDIRMAN Sudirman (Adaara: Jurnal Manajemen Pendidikan Islam, 2019)
Abstract. Core schools deserve to be models from other schools, especially in terms of curriculum implementation. This paper is a descriptive which aims to describe the curriculum implementation process that should be done in elementary school. The Curriculum of 2013 as a form of educational innovation in Indonesia requires various adjustments, especially in the process of implementation. The right curriculum implementation strategy in the presence of an innovation curriculum is teacher oriented. There are three effective teacher-oriented strategies, namely adjusting the mindset, developing new cultures in school and developing the curriculum. The strategy of the O'Mallay and Chamot Model learning process and the Oxford Model Strategy is very feasible to apply in elementary schools with reference to the 2013 Curriculum. Teachers must be able to apply effective, varied and adaptive learning strategies in order to develop students' learning strategies maximally.